Lactate Profiling and the Agreement Among Various Lactate Threshold Methods in Professional and Youth Soccer Players - Marcos Michaelides; Koulla Parpa (Applied Sciences)
The lactate threshold (LT) and the associated running velocities are important markers used to define physical readiness and prescribe exercise intensity in athletes. This study examined blood LT during maximal cardiopulmonary exercise testing using four methods: visual inspection, log-to-log transformation, the Dmax method, and the 4 mmol/L fixed blood lactate accumulation (FBLA) method. The participants included 96 soccer players, comprising 52 professional (27.37 ± 5.67 years) and 44 elite youth players (16.20 ± 0.8 years). A total of 554 capillary blood lactate samples were analyzed. Bland–Altman and ICC analyses for running velocities, determined using the four LT detection methods, demonstrated poor agreement in both groups. Results indicated that the youth players had significantly (p < 0.05) higher V̇O2 max (59.89 ± 5.6 mL·kg−1·min−1) compared to the professional players (56.43 ± 4.81 mL·kg−1·min−1). However, the professional players had significantly better running performance and running economy. A two-way ANOVA revealed a main effect of playing standard, with professional players exhibiting significantly higher 4 mmol/L FBLA LT compared to youth players. A mixed-design ANOVA indicated a significant (p < 0.01) interaction, with the youth exhibiting higher lactate accumulation only after completing the 18 km/h stage. Therefore, youth and professional players should not use the different LT concepts interchangeably. Additionally, the 4 mmol/L FBLA LT method appears to be more robust for youth soccer players.